1982
DOI: 10.1128/iai.36.2.662-666.1982
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of a mycoplasma mitogen for lymphocytes from human and various animal hosts

Abstract: Spleen lymphocytes from Lewis and Buffalo rats and peripheral blood lymphocytes from 10 human donors exhibited high levels of transformation when exposed to Mycoplasma arthritidis supernatants. In contrast, spleen lymphocytes from rabbits and guinea pigs and peripheral blood lymphocytes from sheep and calves failed to transform when exposed to M. arthritidis supernatants. The lymphocytes from all hosts were transformed in the presence of phytohemagglutinin or concanavalin A or both Serological studies failed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…For example, spleen cells of mice possessing the haplotypes H-2'' or H-2'' were reactive, whereas mice of the haplotypes H-2'', H-2f, H-21, and H-2' were non-reactive. MAS is also capable of stimulating human peripheral lymphocytes and those of rat spleens [6]. In the present study we have investigated several inbred rat strains to test whether there was a similar dependency of the MAS response on the MHC, the RTI system [9], as previously reported in mice.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…For example, spleen cells of mice possessing the haplotypes H-2'' or H-2'' were reactive, whereas mice of the haplotypes H-2'', H-2f, H-21, and H-2' were non-reactive. MAS is also capable of stimulating human peripheral lymphocytes and those of rat spleens [6]. In the present study we have investigated several inbred rat strains to test whether there was a similar dependency of the MAS response on the MHC, the RTI system [9], as previously reported in mice.…”
supporting
confidence: 54%
“…The recent studies of Cole et al [6] showed MAS to be a potent mitogen for lymphocytes of several species, whereas lymphocytes of some other species were non-responsive. Responding species included humans, rats, and mice.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether rats, which have an overall V , genomic composition almost identical to that of mice (29), respond to MAM in a similar manner, we assessed the responses of spleen cells from a strain of rats known to be a high responder to this mitogen (Lewis rats) (10,30). As indicated in Figure 1, transcript levels for rat V , (rV& 5.1, 6, 8.1, and 8.2 were strongly enriched in these cultures but rVp8.3, in contrast to mV,8.3, was not engaged.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, mycoplasma-infected tumor cell lines have been reported to produce a higher incidence of metastasis (Stackpole et al 1988), as well as an increased invasiveness (Dudler et al 1988). Furthennore, difTerent mycoplasmas have been recognized to be polyclonal mitogens for both B and/or T celts from various species in an MHC-restricted or -unrestricted way; the mitogenic effects are host-specific and more or less cell type-specific (Cole et al 1982, Naot et al 1977. It has also been demonstrated that mycoplasmas can induce Ig secretion from B lymphocytes, as well as secretion of various cytokines from several cell types.…”
Section: Mycoplasmas and The Immune Systemmentioning
confidence: 99%
“…Various mycoplasma strains including M. fermentans, M. pneumoniae, and M. arthritidis have been discovered to be polycional activators for T lymphocytes of several species including mice, rat and human (Naol et al 1977, Cole et al 1982; human T cells are activated by all three strains. Besides acting as a polyclonal activator in vivo, M. pulmonis has been shown to be mitogenic in vitro for both rat and mice T and B cells (Naot et al 1979a); membrane proteins are the essential component of this activity, whereas isolated membrane lipids are devoid of any mitogenicity (Naot et al 1979b).…”
Section: Mycoplasma Effects On T Lymphocytes In Vitromentioning
confidence: 99%